Isotopic, chemical and crystallographic characteristics of first- year sea ice from Breid Bay (Princess Ragnhild Coast<>9d\Antarctica) - Tison, Jean-Louis; Haren, J (1989)
A detailed profile of the ice fabric, the deuterium content and the sodium concentration of a 1.64 m long, first-year sea-ice core from Breid Bay, near Syowa station (Antarctica), is described. It is proposed that the topmost part of the core consists of frazil ice produced by wind- and wave-induced turbulence. Once a consolidated ice cover is provided, the growth proceeds at a slower rate, through congelation ice formation and frazil ice production, initiated by thermohaline convection processes in the water column. The lower alternate layers of fine grained congelation ice and frazil ice could result from cyclic thermal and salinity regimes at the ice-water interface, connected with the major meteorological events of the year. -from Authors SCOPUS: NotDefined.j info:eu-repo/semantics/published